On a nonstationary loading at a half-plane surface under mixed boundary conditions - Kubenko, V.D. (Reports of the National Academy of Sciences of Ukraine, 2014)
The problem to determine a stressed state of the elastic half-plane under a nonstationary normal loading is considered. A mixed boundary problem is formulated, and its solution is built with using the Laplace and Fourier integral transformations. Exact inverse transforms are evaluated. As a result, the analytical solution is obtained. It determines a stress and a displacement at an arbitrary point of the half-plane at an arbitrary moment of time.